Raça, igualdade e trauma: a função do direito na inclusão/ exclusão dos negros na diferenciação social brasileira - Azevedo, Guilherme de (Universidade do Vale do Rio dos Sinos, 2016)
The present thesis focus on observation the role of law in the inclusion/exclusion of black community during the development of the functional differentiation of Brazilian society. The research seeks to investigate, in historical-sociological perspective, how the system of law reacted, and reacts, to the paradoxical dynamics between two scenarios: the expansion of the visibility of the social indicators data which empirically proves the processes integrative exclusion of the black community in Brazil, and the low production of normative expectations regarding this inequality along the Brazilian social differentiation. This relationship creates contradictory political representations, such as the presence of a systemic dynamic of institutional racism, combined with the image (self-description) of racial democracy in Brazil. Therefore, the thesis proposes as a research problem the possibility that the legal system would have operated throughout Brazilian social differentiation to naturalize the exclusion of black people in Brazil (racial democracy), through the non-generalization of normative expectations that contributed systemically for the formation of self-descriptions of racial inequality and, with this, helping in the constitution of racism as an important trauma of the democracy in Brazil. As a general objective, the target is to observe the juridical structures that represent the racial subject, in historical-evolutionary perspective, to help understanding the function of the law system in the formation of the semantics of racial equality in Brazil. Moreover, it is necessary to point out that the differentiation process of these structural couplings, such as property rights and the formal construction of citizenship (as tension between state/black movement), to the role of the black people as a collective subject in the struggle for human rights in the International scene. That is a key to understand the subject of inclusion/exclusion of black people along the forms of the structuring of democracy in Brazilian society.
Keywords: Raça; Trauma; Igualdade; Exclusão; Race; Trauma; Equality; Exclusion; ACCNPQ::Ciências Sociais Aplicadas::Direito